Unfolded Protein Response in Arabidopsis - Ruberti, Cristina (Methods Mol Biol, 2018)
The unfolded protein response (UPR) is a highly regulated signaling pathway that is largely conserved across eukaryotes. It is essential for cell homeostasis under environmental and physiological conditions that perturb the protein folding in the endoplasmic reticulum (ER). Arabidopsis is one of the outstanding multicellular model systems in which to investigate the UPR. Here, we described a protocol to induce the UPR in plants, specifically arabidopsis, and to estimate their ability to cope with ER stress through the quantification of physiological parameters.